Measure of Noncompactness of Matrix Operators on Some New Difference Sequence Spaces of Order mth - Serkan Demiriz (Journal of New Results in Science)
Kızmaz [13] studied the difference sequence spaces ℓ∞(∆), c(∆) and c(∆)